The convergence of quantum-dot-mediated fluorescence resonance energy transfer and microfluidics for monitoring DNA polyplex self-assembly in real time - Ho, Yi-Ping (2009)
We present a novel convergence of quantum-dot-mediated fluorescence resonance energy transfer (QD-FRET) and microfluidics, through which molecular interactions were precisely controlled and monitored using highly sensitive quantum-dot-mediated FRET. We demonstrate its potential in studying the kinetics of self-assembly of DNA polyplexes under laminar flow in real time with millisecond resolution. The integration of nanophotonics and microfluidics offers a powerful tool for elucidating the formation of polyelectrolyte polyplexes, which is expected to provide better control and synthesis of uniform and customizable polyplexes for future nucleic acid-based therapeutics.